Investigate of Microhardness and Microstructure of Ti-Ni-Nb-X (Ta and V) Shape Memory Alloys - Balci, Esra; Dagdelen, Fethi (My University, 2021)
In this study, based on designed Ti-50Ni, Ti-27Ni-23Nb, and Ti-27Ni-19Nb-4X (Ta and V) SMAs were prepared using arc melting. The\rmicrohardness and microstructure of the prepared alloys were examined. The optical microscope (OM) and Scanning Electron Microscopy\r(SEM) images can be noted that Nb, Ta, and V addition in substitution to nickel causes a change in the microstructure morphology of TiNi\rShape Memory Alloy at room temperature. The microhardness results shown that when V and Ta elements were added to SMAs, the\rmicrohardness of the alloys was significantly increased. Microhardness measurements were determined by taking the alloys from random\rpositions. The microhardness value of equal atomic Ti-Ni SMA was found to 243 HV0.3. This value was determined to 354 HV0.3 in the\rTi-27Ni-23Nb ternary SMA. By the addition of Ta into the Ti-Ni-Nb alloy, the microhardness value was enhanced to approximately 380\rHV0.3, additionally, moreover, by adding Vanadium element to the ternary alloy, the microhardness was increased to about 500 HV0.3.
Keywords: TiNiNbV; Shape Memory Alloy; Optical Microscope; TiNiNbTa